Cost Effective Method for Detecting Clone Nodes in Wireless Sensor Network (International Journal of Engineering and Computer Science, 2018)
In most of wireless sensor application security is one of the prime concern. Generally sensor nodes are not equipped with any tamper resistant hardware and they are deployed in a hostile environment, so the chance of occurring attacks should be greater. In node clone attack adversary will capture few nodes from the network, retrieving its credentials and creating large number of clones by reprogramming the nodes. And these clones may have the ability to subvert the whole network. Thus the detection of node clone attacks in a wireless sensor network is therefore a fundamental problem. In distributed environment many protocols are available to detect the clone attack. Thus far, various schemes have been proposed to detect replicas; however, most of them require expensive hardware like global positioning system (GPS) to obtain the location of a sensor node. In general, sensor nodes are equipped with limited set of resources, to suit for resource constraint sensor application; hence it is not practical to employ additional devices like GPS in them for the detection process. In Cost Effective Method for Detecting Clone Nodes in WSN (CEMDCN) protocol introducing a low priced and energy efficient solution for detecting clone nodes in wireless sensor network without using GPS in them. Extensive simulation shows that proposed method is efficient in terms of detection probability, memory and communication overhead. Also this is a better clone detection scheme in resource constraint sensor application.